Social Media Algorithms - Jain, Deepak (Indian Journal of Computer Science, 2022)
The need and desire to communicate information, ideas, and emotions has been strong in humans. It has evolved from traditional forms such as story-telling, plays, paintings, carvings, community gatherings to digital forms of communication. As digital social media platforms are growing at a rapid pace and are touching billions of people worldwide, it becomes important to understand how these platforms work and their effect on users and the society. The present paper analyzes social media algorithms, how they rank content, and how Machine Learning drives these algorithms. The shortcomings of social media algorithms and their future are also discussed.